Current Trends in Scleral Lens Prescription, Management, and Evaluation. Issue 2 (10th February 2023) - Schornack, Muriel M.; Nau, Cherie B.; Harthan, Jennifer; Shorter, Ellen; Nau, Amy; Fogt, Jenny
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To report current trends in scleral contact lens prescription and management, including lens designs prescribed, care products recommended, and procedures performed during routine scleral lens (SL) evaluation. Methods: An online survey was designed by the Scleral Lenses in Current Ophthalmic Practice Evaluation study team and administered to eye care practitioners attending a specialty contact lens meeting. The survey was available from November 8, 2019, through March 31, 2020. Participants' demographic data were collected, along with information on lens diameters, landing zone (LZ) designs, recommended care products, and components of routine SL evaluation. Results: In total, 715 participants responded to at least one of the survey items of interest. Most lenses prescribed (63%) were 16 mm or more in diameter. Lenses with toric LZs were the most frequently prescribed (48%), followed by spherical (40%), quadrant-specific (8%), and impression-based or image-based designs (3%). Most participants (61%) recommended hydrogen peroxide products for lens care. Nonpreserved saline in a single-use vial was most frequently recommended to fill the bowl of the lens before application. Intraocular pressure was measured during SL evaluation by 45% of participants; 38% of participants routinely measured corneal thickness. Conclusions: Practitioners increasingly are prescribing SLs with advanced LZ designs. Most practitioners recommend hydrogen peroxide–based disinfection systems and single-use vials of nonpreserved saline for lens care and application. Because differences in components of routine SL evaluations were reported, clinicians may benefit from reaching a consensus on essential components of SL evaluation.